PENINGKATAN KUALITAS PEMBELAJARAN PKn MELALUI MODEL TEAMS GAMES TOURNAMENT DENGAN MEDIA TEKA-TEKI SILANG - Kasmuri Kasmuri (MEDIA DIDAKTIKA, 2021)
The purpose of this study was to improve the quality of Civics Education learning. This research was carried out using a classroom action research design with four stages each cycle, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. This research was conducted in two cycles, each cycle two meetings. The subjects of this study were teachers and fourth grade students of SDN Pangkatrejo I Kec. Lamongan. The variables of this study are teacher skills, student activities, and student learning outcomes. Data is stacked with technical tests and non-tests. The results showed that the Teams Games Tournament learning model with crossword puzzle media could improve teacher skills, student activities, and learning outcomes of fourth grade students at SDN Pangkatrejo I Kec. Lamongan, Kab. Lamongan. Suggestions formulated are teachers can apply the Teams Games Tournament learning model with media crossword puzzles as an alternative solution to improve teaching skills to be more innovative, student activities to be able to participate more, and student learning outcomes increase.